Inventarisasi Tumbuhan Famili Fabaceae di Desa Tabing Rimbah Kecamatan Mandastana Kabupaten Barito Kuala - Audi Athfin Mawafda; Danang Biyatmoko; Bunda Halang (Biocaster : Jurnal Kajian Biologi, 2026)
Indonesia is one of the countries with the highest level of biodiversity in the world, including plant diversity from the Fabaceae family which has an important role ecologically and economically. The Fabaceae family contributes to maintaining soil fertility through nitrogen fixation capabilities, and is widely used as a source of food, medicine, animal feed, and shade plants. The existence of Fabaceae plants can be found in various types of ecosystems, such as swamps, forests, and agricultural land. This study aims to inventory the diversity of plant species of the Fabaceae family found in Tabing Rimbah Village, Mandastana District, Barito Kuala Regency, South Kalimantan. The research method used is an exploratory approach through direct observation in the field, recording morphological characters, photo documentation, and species identification using taxonomic literature and PlantNet applications. The results of the study showed that as many as 16 species of plants from the Fabaceae family were found with variations in habitus in the form of herbs, shrubs, and trees. The diversity of these species shows that the environmental conditions in Tabing Rimbah Village are quite supportive of the growth and development of Fabaceae plants. These findings affirm the importance of biodiversity inventory as a basis for sustainable conservation and management of local biological resources.